2023
DOI: 10.1093/pnasnexus/pgad282
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 infection leads to Tau pathological signature in neurons

Cristina Di Primio,
Paola Quaranta,
Marianna Mignanelli
et al.

Abstract: COVID-19 has represented an issue for global health since its outbreak in March 2020. It is now evident that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection results in a wide range of long-term neurological symptoms and is worryingly associated with the aggravation of Alzheimer’s disease. Little is known about the molecular basis of these manifestations. Here, several strain variants were used to infect SH-SY5Y neuroblastoma cells and K18-hACE C57BL/6J mice. The Tau phosphorylation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Despite the amyloid pathology, tau pathology has also been correlated with SARS-CoV-2 infection. Recently, using SH-SY5Y neuroblastoma cells and K18-hACE C57BL/6J mice, Di Primio et al found that SARS-CoV-2 infection promotes tau phosphorylation and increases tau aggregation [ 49 ]. In addition, hyperphosphorylated tau was further observed in the cortex of the coronavirus mouse model of COVID-19 even 12 months post-infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the amyloid pathology, tau pathology has also been correlated with SARS-CoV-2 infection. Recently, using SH-SY5Y neuroblastoma cells and K18-hACE C57BL/6J mice, Di Primio et al found that SARS-CoV-2 infection promotes tau phosphorylation and increases tau aggregation [ 49 ]. In addition, hyperphosphorylated tau was further observed in the cortex of the coronavirus mouse model of COVID-19 even 12 months post-infection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 Despite the absence of definitive causal links between SARS-CoV-2 infection and AD, 14,[17][18][19][20] the examination of preclinical mouse models presents a valuable opportunity to gain crucial insights into the relationship between SARS-CoV-2 and AD. SARS-CoV-2 infection has been documented to induce hyperphosphorylated tau (p-tau) pathology in various models, encompassing human neuronal cell lines, 21 human neurons, 22 as well as in animal subjects such as Syrian golden hamsters, 23 K18-hACE2 and C57BL/6J mice. 7 Given the wellestablished connection between tau pathology and cognitive dysfunction in AD, 24,25 it is paramount to investigate the development of SARS-CoV-2-induced tau pathology within brain regions linked to cognitive function using preclinical mouse models.…”
Section: Differential Host Immune Responses In Hace2ki Mice To Sars-c...mentioning
confidence: 99%
“…The generation of amyloid-beta and hyperphosphorylated tau, molecules that we currently recognize as inducers of innate immunity ( Rexach et al, 2020 ; Roy et al, 2020 ; Jin et al, 2021 ; Roy et al, 2022 ; Vavougios et al, 2022a ; Udeochu et al, 2023 ), can in turn sustain pathogenic IFN-I in a feed-forward manner acting as danger associated molecular pattern ( Asai et al, 2015 ; Bolós et al, 2016 ) in a process that has been shown to prime microglia towards phenotypes specifically associated with the earlier stages of neurodegenerative disease ( Roy et al, 2020 ; Jin et al, 2021 ; Magusali et al, 2021 ; Kim et al, 2022 ; Udeochu et al, 2023 ). This aspect of our model, previously predicting beta amyloidosis and tauopathy based on the IFN-I response secondary to SARS-CoV-2 infection ( Ramani et al, 2020 ; Vavougios et al, 2021a , b , 2022a , b , c ; Di Primio et al, 2023 ) has been independently validated ( Ramani et al, 2020 ; Green et al, 2022 ; Käufer et al, 2022 ; Ma et al, 2022 ; Reiken et al, 2022 ; Di Primio et al, 2023 ; Suzzi et al, 2023 ). A notable part of this feed-forward process is that microglial activation may be sustained via sterile DAMPs as IFN-I activators ( Roy et al, 2020 ) such as exosomal or insoluble tau ( Asai et al, 2015 ; Bolós et al, 2016 ) and errant nucleic acids ( Roy et al, 2020 ).…”
Section: Type I Interferon Signaling Dysregulation In the Brain Is A ...mentioning
confidence: 99%
“…In the fused cortical blood vessel organoid model, tauopathy, beta amyloidosis and microglial activation was also noted as a result of SARS-CoV-2 infection ( Kong et al, 2023 ). Notably, aberrant tau phosphorylation secondary to SARS-CoV-2 infection has also been observed in SH-SY5Y neuroblastoma cells ( Di Primio et al, 2023 ). Type I interferon responses were elicited by SARS-CoV-2 infection of forebrain organoids, potentially in variant-dependent manner ( Hou et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%